2012
DOI: 10.1007/s10994-012-5281-z
|View full text |Cite
|
Sign up to set email alerts
|

PAMR: Passive aggressive mean reversion strategy for portfolio selection

Abstract: This article proposes a novel online portfolio selection strategy named "Passive Aggressive Mean Reversion" (PAMR). Unlike traditional trend following approaches, the proposed approach relies upon the mean reversion relation of financial markets. Equipped with online passive aggressive learning technique from machine learning, the proposed portfolio selection strategy can effectively exploit the mean reversion property of markets. By analyzing PAMR's update scheme, we find that it nicely trades off between por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 67 publications
1
86
0
1
Order By: Relevance
“…Although some recently proposed mean reversion algorithms [46,45] have achieved promising results on many real datasets, they might perform extremely poorly on certain datasets, such as the DJIA dataset [8]. Comparing with Borodin et al [8], which exploits multi-period correlation, we found that the assumption of single-period prediction may attribute to the performance degradation.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…Although some recently proposed mean reversion algorithms [46,45] have achieved promising results on many real datasets, they might perform extremely poorly on certain datasets, such as the DJIA dataset [8]. Comparing with Borodin et al [8], which exploits multi-period correlation, we found that the assumption of single-period prediction may attribute to the performance degradation.…”
mentioning
confidence: 61%
“…Li et al [46] proposed Passive Aggressive Mean Reversion (PAMR) strategy, which exploits the mean reversion property with the Passive Aggressive (PA) online learning [53,17]. The main idea of PAMR is to design a loss function of (b; x t ) in order to reflect the mean reversion property, that is, if the expected return based on last price relative is larger than a pre-defined threshold, the loss will linearly increase; otherwise, the loss is zero.…”
Section: Follow-the-loser Approachesmentioning
confidence: 99%
See 3 more Smart Citations